Comparative analysis of digital artifact persistence between file format - Saari, Anati Dalila; Mohamad, Kamaruddin Malik (Penerbit UTHM, 2017)
As we know digital forensics is a scientific examination and analysis of data that when it held on, or where it is retrieved from so that the information collected can be used as evidence in a court of law. Nowadays, digital evidence are very useful to provide when case in court. The deleted file of document, audio or image can be recover back as digital artifact [1]. Therefore, it is very clear from the experience that digital artifact are important witnesses to care.